Pathophysiology and Clinical Management of Moderate and Severe Traumatic Brain Injury in the ICU - Sheriff, Faheem G.; Hinson, Holly E. (Seminars in Neurology, 2015)
Moderate and severe traumatic brain injury (TBI) is the leading cause of morbidity and mortality among young individuals in high-income countries. Its pathophysiology is divided into two major phases: the initial neuronal injury (or primary injury) followed by secondary insults (secondary injury). Multimodality monitoring now offers neurointensivists the ability to monitor multiple physiologic parameters that act as surrogates of brain ischemia and hypoxia, the major driving forces behind secondary brain injury. The heterogeneity of the pathophysiology of TBI makes it necessary to take into consideration these interacting physiologic factors when recommending for or against any therapies; it may also account for the failure of all the neuroprotective therapies studied so far. In this review, the authors focus on neuroclinicians and neurointensivists, and discuss the developments in therapeutic strategies aimed at optimizing intracranial pressure and cerebral perfusion pressure, and minimizing cerebral hypoxia. The management of moderate to severe TBI in the intensive care unit is moving away from a pure “threshold-based” treatment approach toward consideration of patient-specific characteristics, including the state of cerebral autoregulation. The authors also include a concise discussion on the management of medical and neurologic complications peculiar to TBI as well as an overview of prognostication.
Keywords: severe traumatic brain injury; pathophysiology; multimodality monitoring; intensive care unit